Nanoparticles of Esterified Polymalic Acid for Controlled Anticancer Drug Release() - Lanz-Landázuri, Alberto (2014)
[Image: see text] Esterification of microbial poly(malic acid) is performed with either ethanol or 1-butanol to obtain polymalate conjugates capable to form nanoparticles (100–350 nm). Degradation under physiological conditions takes place with release of malic acid and the corresponding alcohol as unique degradation products. The anticancer drugs Temozolomide and Doxorubicin are encapsulated in nanoparticles with efficiency of 17 and 37%, respectively. In vitro drug release assays show that Temozolomide is almost completely discharged in a few hours whereas Doxorubicin is steadily released along several days. Drug-loaded nano-particles show remarkable effectiveness against cancer cells. Partially ethylated poly(malic acid) nano-particles are those showing the highest cellular uptake.